TLRs, Alcohol, HCV, and Tumorigenesis - Keigo Machida (Gastroenterology Research and Practice)
Chronic liver damage caused by viral infection, alcohol, or obesity can result in increased risk for hepatocellular carcinoma (HCC). Ample epidemiological evidence suggests that there is a strong synergism between hepatitis C virus (HCV) and alcoholic liver diseases (ALD). The Toll-like receptor (TLR) signaling pathway is upregulated in chronic liver diseases. Alcoholism is associated with endotoxemia that stimulates expression of proinflammatory cytokine expression and inflammation in the liver and fat tissues. Recent studies of HCC have centered on cancer-initiating stem cell (CSC), including detection of CSC in cancer, identification of CSC markers, and isolation of CSC from human HCC cell lines. Synergism between alcohol and HCV may lead to liver tumorigenesis through TLR signaling.